The Effect of Health Education on Mom's Knowledge About Advanced Immunization (Boster) in Baduta at Posyandu, Tanjung Asri Village, Sei Dadap District Asahan District Year 2022 - Devi Sagita Saragi (Institute of Computer Science (IOCS), 2022)
Immunizations for children should be given routinely and completely. Mother's knowledge about follow-up immunization (booster) is very important to be improved to prevent children under two years old (baduta) from getting various diseases that can be prevented through immunization. This study aims to determineThe Effect of Health Education on Mother's Knowledge of Advanced Immunization (Boster) for Baduta at Posyandu Tanjung Asri Village, Sei Dadap District, Asahan Regency in 2022. This research isstudyparametric statistical analysisapproachone-group pretest-posttest design. This research has been carried out on September 13, 2022 to September 24, 2022. The population is32 people. Sampling usingaccidental samplingwith a sample of 32 people. The results of the study found thatMother's knowledge about follow-up immunization (booster) before being given Health Education at Posyandu Tanjung Asri Village, Sei Dadap District, Asahan Regency in 2022is the majority is not good andMother's knowledge about follow-up immunization (booster) after being given Health Education at Posyandu Tanjung Asri Village, Sei Dadap District, Asahan Regency in 2022 is the majority good. Based on the results of the paired sample t-test, it was found that the p value = 0.001 <0.05. The conclusion in this study is that there areThe Effect of Health Education on Mother's Knowledge of Advanced Immunization (Boster) for Baduta at Posyandu Tanjung Asri Village, Sei Dadap District, Asahan Regency in 2022.Suggestions in this researchTanjung Asri Village, Sei Dadap District, Asahan Regencycontinue to carry out health education that is programmed and carried out continuously to increase mother's knowledge about advanced immunization.